2012
DOI: 10.1007/s00246-012-0504-4
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Congenital Heart Disease and Birth Outcomes

Abstract: This study was undertaken to examine the impact that prenatal diagnosis of congenital heart disease (CHD) has on birth and early neonatal outcomes. The prevalence of prenatally diagnosed CHD has risen over the past decade, but the effect that prenatal diagnosis of CHD has on peripartum decisions remains unclear. No consensus exists on the effect of prenatal diagnosis on neonatal outcomes. Between January 2004 and July 2009, a retrospective chart review of all neonates with CHD admitted to our institution’s neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 33 publications
3
72
2
3
Order By: Relevance
“…Michiko Yamashita 1) , Nobuhiro Hidaka 1) , Shusaku Hayashi 1) , Akemi Irie 2) , Akiko Miyagi 2) , Yukiko Kawazu 3) , Noboru Inamura 3) , Futoshi Kayatani 3) , Keisuke Ishii 1) , Nobuaki Mitsuda…”
Section: Results Of Fetal Cardiac Ultrasonographic Screening In Our Iunclassified
See 1 more Smart Citation
“…Michiko Yamashita 1) , Nobuhiro Hidaka 1) , Shusaku Hayashi 1) , Akemi Irie 2) , Akiko Miyagi 2) , Yukiko Kawazu 3) , Noboru Inamura 3) , Futoshi Kayatani 3) , Keisuke Ishii 1) , Nobuaki Mitsuda…”
Section: Results Of Fetal Cardiac Ultrasonographic Screening In Our Iunclassified
“…Department of 1) Maternal Fetal Medicine, 2) Laboratory Medicine, 3) Pediatric Cardiology, Osaka Medical Center And Research Institute For Maternal And Child Health, Osaka, Japan…”
Section: )mentioning
confidence: 99%
“…This study also demonstrated that operative mortality and hospital stay in neonates with HLHS were not affected by prenatal diagnosis. 10 However, in 2013, Landis et al 11 reported that prenatal diagnosis of all CHD did not have an impact on preoperative or predischarge mortality.…”
Section: Benefits Of Prenatal Diagnosismentioning
confidence: 99%
“…Prenatal detection of congenital cardiovascular anomalies is considered beneficial for the neonate, allowing for a scheduled delivery and proactive planning of further actions (including interventions and treatment) [2,3]. Without a doubt, echocardiography is the first choice to visualize fetal cardiovascular defects.…”
Section: Introductionmentioning
confidence: 99%